Mushroom biome foodtruck / Iqmal Hariz Rizal ...[et al.] - Rizal, Iqmal Hariz; Muhamad Khair, Hannan Asyrawi; Mohd Salleh, Fairuz A'ain; Mohd Hisham, Ahmad Muaaz; Mohd Fauzi, Mohamad Danial Najmi (2022)
Our company's name is Mushroom Biome. It's the result of combining the words "mushroom" and "biome." Mushroom Biome is also a food truck that specialises on Malaysian fast cuisine, with mushrooms as our major menu item. Plus, instead of utilising regular oyster mushroom, our mushroom is a handcrafted mushroom created with enoki mushroom. The major goal of this business is to expand the number of local fast-food restaurants that provide the same product as non-local mushroom joints but at a lower cost. The Mushroom Biome food truck will debut on February 14th, 2022. We chose this form of business because we saw an opportunity to expand our existing business. This is because food goods, particularly fast-food products, are currently in high demand and will continue to be so in the future. Furthermore, several businesses have grown in recent years as a result of providing high-quality meals to their clients. The reason we chose mushroom as our main course is that all Malaysians, regardless of religion or race, like eating mushrooms. In addition, we may use the mushroom to create a variety of menus. Every year, this business plan will be used to analyse the company from the beginning. It's also critical to safeguard our financial situation. This is because banks or other investors may require a copy of our business plan in order to determine the profitability of the company. This business plan will be very important for us to operate our firm because it includes an introduction to our company, marketing plan, administration plan, operational plan, and financial plan. For our food truck, we chose only one location where we can park our vehicle and attract many clients, which is the food truck area. This location also provides essential utilities including water, electricity, Wi-Fi, and parking. Because we are in the food service industry, we always require a large supply of water. We also planned to sell our business at night, so having electricity is vital. Furthermore, we chose Wi-Fi-enabled sites because many people currently prefer to eat in places with decent internet connections.